Optimized radiofrequency coil setup for MR examination of living isolated rat hearts in a horizontal 9.4T magnet. - Lohezic, M; Bollensdorff, C; Korn, M; Lanz, T; Grau, V; Kohl, P; Schneider, J (Wiley, 2015)
PURPOSE: (i) To optimize an MR-compatible organ perfusion setup for the nondestructive investigation of isolated rat hearts by placing the radiofrequency (RF) coil inside the perfusion chamber; (ii) to characterize the benefit of this system for diffusion tensor imaging and proton ((1) H-) MR spectroscopy. METHODS: Coil quality assessment was conducted both on the bench, and in the magnet. The benefit of the new RF-coil was quantified by measuring signal-to-noise ratio (SNR), accuracy, and precision of diffusion tensor imaging/error in metabolite amplitude estimation, and compared to an RF-coil placed externally to the perfusion chamber. RESULTS: The new design provided a 59% gain in signal-to-noise ratio on a fixed rat heart compared to using an external resonator, which found reflection in an improvement of living heart data quality, compared to previous external resonator studies. This resulted in 14-29% improvement in accuracy and precision of diffusion tensor imaging. The Cramer-Rao lower bounds for metabolite amplitude estimations were up to 5-fold smaller. CONCLUSION: Optimization of MR-compatible perfusion equipment advances the study of rat hearts with improved signal-to-noise ratio performance, and thus improved accuracy/precision. Magn Reson Med, 2014. © 2014 The Authors. Magnetic Resonance in Medicine Published by Wiley Periodicals, Inc. on behalf of International Society of Medicine in Resonance. This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution, and reproduction in any medium, provided the original work is properly cited.